Analisis Kebijakan Alih Fungsi Alas Kethu Kabupaten Wonogiri - Cahyono, Yudi Sri; Sutanto, Djoko (Responsibilitas, 2010)
Abstract Development is processing social change towards better public order. The civilization of man will not reach form that is now if not happened change process of social that is continuous, though with variety intensity during then. However, development as man effort who is conscious, planned and institutes, be unique case at XX century more than a free social process assessed. Development obtains concept character trancendental, as metadisciplinary, phenomenom, even obtains form as ideology, ideology of developmentalism. Keyword: perubahan masyarakat, pembangunan.